2010
DOI: 10.1088/1742-6596/225/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Free volume in Zr-based bulk glassy alloys studied by positron annihilation techniques

Abstract: The value of the positron lifetime for hypoeutectic BG alloy is virtually the same. Additionally, the CDB ratio curve for hypoeutectic alloy dose not match that for eutectic alloy in an electron momentum region around 0.015 m 0 c, indicating that the fraction of Zr atoms around the free volume in hypoeutectic BG alloy is greater than that in eutectic BG alloy. Moreover, the CDB results show that the local structure around free volume for hypoeutectic BG alloy is different from that for eutectic BG alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Generally, thermally activated STZs initiate around free-volume sites under an applied shear stress because high elastic strain at free-volume sites energetically promotes STZ formation. From the studies on the positron annihilation analysis of Zr-Cu-Al BMGs, free volume in ternary hypoeutectic Zr 60 Cu 30 Al 10 BMG is surrounded by a higher fraction of Zr atoms as compared to the eutectic Zr 50 Cu 40 Al 10 BMG, which indicates that the higher fraction of Zr-Zr atomic pairs in this alloy is probably accompanied with more free volume [24]. Moreover, it is previously reported that a large compressive plastic strain could be achieved due to a large amount of randomly distributed free volume induced in Zr-Cu-Al-Ti BMG system by Ti minor alloying [25].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, thermally activated STZs initiate around free-volume sites under an applied shear stress because high elastic strain at free-volume sites energetically promotes STZ formation. From the studies on the positron annihilation analysis of Zr-Cu-Al BMGs, free volume in ternary hypoeutectic Zr 60 Cu 30 Al 10 BMG is surrounded by a higher fraction of Zr atoms as compared to the eutectic Zr 50 Cu 40 Al 10 BMG, which indicates that the higher fraction of Zr-Zr atomic pairs in this alloy is probably accompanied with more free volume [24]. Moreover, it is previously reported that a large compressive plastic strain could be achieved due to a large amount of randomly distributed free volume induced in Zr-Cu-Al-Ti BMG system by Ti minor alloying [25].…”
Section: Resultsmentioning
confidence: 99%